1999
DOI: 10.1074/jbc.274.8.4801
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Double-stranded RNA-activated Protein Kinase in the Synergistic Activation of Nuclear Factor-κB by Tumor Necrosis Factor-α and γ-Interferon in Preneuronal Cells

Abstract: Tumor necrosis factor-␣ (TNF-␣) and ␥-interferon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 66 publications
2
62
0
Order By: Relevance
“…The need of PKR kinase activity for NF-kB activation is also supported by the previous observation that 2-aminopurine, an inhibitor of PKR catalytic activity, is able to inhibit NF-kB activation induced by PKR (Kumar et al, 1994;Cheshire et al, 1999). However, another study has suggested that PKR kinase dead mutant is able to activate NF-kB (Chu et al, 1999).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The need of PKR kinase activity for NF-kB activation is also supported by the previous observation that 2-aminopurine, an inhibitor of PKR catalytic activity, is able to inhibit NF-kB activation induced by PKR (Kumar et al, 1994;Cheshire et al, 1999). However, another study has suggested that PKR kinase dead mutant is able to activate NF-kB (Chu et al, 1999).…”
Section: Discussionsupporting
confidence: 54%
“…It has been shown that PKR-mediated activation of NF-kB can be inhibited by blocking PKR catalytic activity using the chemical inhibitor 2-aminopurine (Kumar et al, 1994;Cheshire et al, 1999). However, more recently another study suggested that expression of a PKR K296R point mutant lacking catalytic activity, was able to activate the IKK complex, (Chu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Published studies have shown that combined TNF and IFNg treatment enhanced NF-kB activation in preneuronal cells and fibroblasts. 31,33,34 Ouaaz et al 31 demonstrated that cytotoxicity of TNF was enhanced by addition of IFN-g in mouse embryonic fibroblasts. This cytotoxicity was shown to be because of apoptosis induced by interaction of Fas and FasL, and the activation of NF-kB induced by combined treatment with TNF and IFN-g was demonstrated to function in a proapoptotic manner.…”
Section: Discussionmentioning
confidence: 99%
“…The link between the TNF signaling pathway and PKR activation also remains to be determined. There is a de®ciency in TNF signaling of NF-kB in PKR null cells or in cells expressing transdominant mutants of PKR that is manifest in an inability to sustain NF-kB activation (ZamanianDaryoush et al, 1999;Chesire et al, 1999). Therefore, the defect in apoptosis induction by TNFa in PKR null cells could be due in part to a failure to upregulate the expression of antiapoptotic genes dependent on NF-kB.…”
Section: Signaling Via Pkrmentioning
confidence: 99%